Emergency department wait time in Newfoundland and Labrador, Canada: Trends and projections of physician initial assessment 2015–2026 - Moein Yoosefi; Armin Hatefi; Hensley H. Mariathas; Christopher Patey; Paul Norman; Oliver Hurley; Bahareh Ahmadzadeh; Aswathy Geetha Manukumar; Anna Walsh; Shabnam Asghari (PLoS ONE, 2026)
Background This study aims to analyze and project the trend of physician initial assessment (PIA) time in rural and urban emergency departments (ED’s) across Newfoundland and Labrador, Canada, considering different levels of the Canadian Triage and Acuity Scale (CTAS). Methods The data for this study were obtained from the Newfoundland and Labrador Health Services Digital Health Department (NLHS-DH), sourced from electronic health records of emergency departments in Newfoundland and Labrador, from April 2015 to the end of 2021. A mixed-effects model was used to analyze trends in PIA time. This process also projects the mean PIA time from 2015 to 2026 across different rural/urban areas and CTAS levels (3–5). Furthermore, the Monte Carlo simulation methods are employed to estimate the uncertainty interval associated with PIA time. Results Our projection showed that the overall mean PIA time in Newfoundland and Labrador emergency departments is expected to increase from a model-estimated 1 hour and 32 minutes in 2015 to a projected 2 hours and 59 minutes in 2026, corresponding to a 94.3% increase over the study period. This increasing trend is observed across various rural and urban areas, including varying CTAS levels. Urban regions are projected to have the biggest change, with a PC of 126.73% as compared to rural areas. The greatest overall change in PIA time is from 1 hour 25 minutes in 2015 to 3 hours 44 minutes in 2026 for CTAS 5 (PC = 163.34). However, when considering rural and urban areas separately, the most notable shift occurs for CTAS level 3 for both areas. Conclusion PIA time trends and patterns have drastically changed across CTAS levels 3–5 in both rural and urban areas. An intervention is needed to control the increasing delay in PIA time, with a particular emphasis on urgent patients residing in rural areas.